Clinical and cost-effectiveness of telehealth for Indigenous and culturally and linguistically diverse (CALD) people: a scoping review. Issue 1 (2nd January 2023) - Cardona, Magnolia; Fien, Samantha; Myooran, Jananee; Hunter, Carol; Dillon, Anne; Lewis, Ebony; Browning, Melissa; Lewis, Lou; Ní Chróinín, Danielle
ABSTRACT: Background: Health inequalities for Indigenous people and culturally diverse patients or remote area dwellers are well established. Models of care such as telehealth might have the potential to reduce the disparity of access to health services for Indigenous and culturally diverse ethnic groups. Objectives: To examine the modalities and clinical and non-clinical effectiveness of telehealth services available to people from Indigenous and culturally and linguistically diverse backgrounds (CALD). Materials and methods: A scoping review of peer-reviewed publications (2000–2021) on the effectiveness of telehealth interventions for Indigenous and CALD groups based on searches of Medline, CINAHL, and PsycInfo and manual searches from reference lists of captured literature reviews. Results: Of the initial 601 articles, 10 met the inclusion criteria (seven of clinical effectiveness and three of non-clinical effectiveness), with participants from the USA, Australia, New Zealand, and Canada, with sample sizes ranging from 19 to 1, 665 participants (overall 327 Indigenous and 2, 030 CALD patients). Telehealth was delivered via telephone or by videoconference—with or without data uploads—and follow-up ranging from 6 months to 5 years. Discussion: The findings suggest that telehealth shows some promise in: diabetes, depression, neuro/cognitive assessment, and health program adherence/service utilisation/cost. However, our confidence in the accuracy of the results is undermined by the mixed quality of designs and outcome measurements, and the high risk of bias derived from not proper random selections and small sample sizes. Conclusions: The available literature suggests acceptable clinical and non-clinical effectiveness of telehealth against usual care in Indigenous and/or CALD groups but methodological limitations diminish their value in informing practice. Therefore, we consider it is premature to use the findings of these primary studies to draw conclusive recommendations about clinical or other effectiveness of telehealth for the two target groups. Further randomised trials with adequate sampling frames and objective outcome assessments are warranted.